2018
DOI: 10.2478/pcssr-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aerobic and Core Exercises on Forced Vital Capacity

Abstract: The aim of the study was to investigate the effect of aerobic and core strength exercises on forced vital capacity in sedentary women. A total of 40 healthy sedentary women (20 in an aerobic-step group and 20 in a core strength exercise group) with a mean age of 34.4±2.4 years participated voluntarily in this study. Two different exercises were applied to the women for 12 weeks, 4 days a week, at the intensity of 70% for 60 minutes. The women's resting heart rate (RHR), maximal oxygen consumption (VO2max), for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Trunk muscle endurance exercises may have a positive influence on respiratory function. 12 Another study, also found that the aerobic and forced vital capacities of the sedentary women showed a parallel increase as a result of the applied 12-week aerobic and core strength exercises and stated that the RHR, VO2max, FEV, and FEV1 respiratory parameters also improved positively. 13 In another study, it was concluded that adding core stabilization exercises to basic deep breathing exercise may be more effective due to the improvements in thoracic mobility.…”
Section: Discussionmentioning
confidence: 92%
“…Trunk muscle endurance exercises may have a positive influence on respiratory function. 12 Another study, also found that the aerobic and forced vital capacities of the sedentary women showed a parallel increase as a result of the applied 12-week aerobic and core strength exercises and stated that the RHR, VO2max, FEV, and FEV1 respiratory parameters also improved positively. 13 In another study, it was concluded that adding core stabilization exercises to basic deep breathing exercise may be more effective due to the improvements in thoracic mobility.…”
Section: Discussionmentioning
confidence: 92%
“…The results showed that the group performing inspiratory muscle training in addition to preseason training had a statistically significant difference in their VO 2 max values compared with the Control Group. Çiçek et al (2018), conducted their studies on 40 female participants. They were divided into two groups: Group Aerobic‐step and Group Core Exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, this study supports the literature. Long‐term exercises not only help increase the strength of the respiratory muscles, but also lead to better physical fitness and respiratory function (Çiçek et al, 2018). As a result, engaging in specific sports or physical activities can help to strengthen the respiratory muscles, improve lung capacity, and achieve effective lung function (FVC, FEV1).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed after the training that the increase in weight, FVC, FVC%, FEV 1 , PEF and FEV 1 /FVC% values of experimental group was significant compared to the control group. This suggests that the respiratory muscles are strengthened by the effect of training [1,30], and it causes high level of the forced vital capacity together with the increase in vital capacity [6]. Lazovic et al (2015) reported that respiratory adaptations occurred with participation in sports activities and these adaptations changed according to the type of activity [16].…”
Section: Discussionmentioning
confidence: 99%